2017
DOI: 10.1163/22119000-12340046
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Investment Treaties and Regional Investment Regulation in Africa: Towards a Continental Investment Area?

Abstract: This article addresses the issue of international investment regulation with a bearing on Africa. It reviews the bilateral investment treaties (BITs) which have been signed by African countries and characterizes intra-African BITs. It also discusses regional investment regulation in the continent and its elements for harmonizing the cluttered ‘spaghetti-bowl’ of investment regimes. Based on the findings and the existing regional integration agenda on investment, the article discusses the viability of an Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, most of the IIAs signed by African states were with non-African states (Paez, 2017) [18] and because of the imbalance of economic power, African states have largely been takers of model IIAs from their counterparts. Furthermore, African arbitrators have been largely under-represented in the investment arbitral "club".…”
Section: Contributions At the Global Levelmentioning
confidence: 99%
“…However, most of the IIAs signed by African states were with non-African states (Paez, 2017) [18] and because of the imbalance of economic power, African states have largely been takers of model IIAs from their counterparts. Furthermore, African arbitrators have been largely under-represented in the investment arbitral "club".…”
Section: Contributions At the Global Levelmentioning
confidence: 99%
“…Despite the burgeoning interest in analysing the impact of BITs on FDI, very few empirical studies on their effectiveness have been conducted in Africa, with a few having a legal background. Páez (2017) reviewed BITs signed by African countries and discussed regional investment regulations within the context of harmonizing investment regimes to establish that the African continental free trade area would be a viable alternative to challenges with current investment regimes. A survey by the Economic Commission for Africa (2016) reported that investment treaties do not attract much FDI since most investments came from countries without BITs.…”
Section: Theoretical Underpinnings and Empirical Literaturementioning
confidence: 99%